Effects of a Safe Transportation Educational Program for Older Drivers on Driving Exposure and Community Participation: A Randomized Controlled Trial. Issue 3 (9th December 2016) - Coxon, Kristy; Chevalier, Anna; Brown, Julie; Clarke, Elizabeth; Billot, Laurent; Boufous, Soufiane; Ivers, Rebecca; Keay, Lisa
Abstract : Objectives: To ascertain whether a safe‐transportation program can change driving exposure while maintaining community participation of older drivers. Design: Randomized controlled trial. Setting: Northwest Sydney. Participants: Drivers aged 75 and older (mean 80 ± 4) (n = 380). Intervention: Intervention group participated in an individualized, one‐on‐one safe‐transportation program adapted from the Knowledge Enhances Your Safety curriculum. A registered occupational therapist delivered the intervention in two sessions held approximately 1 month apart. Measurements: An in‐vehicle monitoring device hardwired into participants' vehicles measured driving exposure. Community participation was measured using the Keele Assessment of Participation. A staging algorithm based on the Precaution Adoption Process Model measured behavior change toward increased and sustained driving self‐regulation. Main outcomes were distance driven per week over 12 months and community participation. Secondary outcomes were behavior change, depressive symptoms, and alternate transportation use. Generalized estimating equations were used to model effect on driving exposure, adjusting for weekly measures, and ordinal regression was used to analyze differences in behavior change profiles between groups using an intention‐to‐treat approach. Results: Participants were randomized after baseline assessment—190 each to the intervention and control groups. One hundred eighty‐three of 190 completed the intervention and 366 of 380 completed the study. On average, participants drove 140 ± 167 km/wk. Although there was no significant difference between the groups in distance driven per week over 12 months (between‐group difference −5.5 km, 95% confidence interval (CI) = −24.5–13.5 km, p = .57), intervention group participants showed greater readiness to engage in self‐regulatory driving practices, such as reporting avoiding driving at night or at rush hours, than control group participants (odds ratio (OR) = 1.6, 95% CI = 1.1–2.3, P = .02). At 12 months, use of alternate transportation was similar (between‐group difference 0.1, 95% CI = −1.4–1.6, P = .90). Although there was no difference in community participation (between‐group difference −0.1, 95% CI = −0.6–0.3, P = .59), older drivers with low function in the intervention group were 3.1 times as likely to report depressive symptoms (95% CI = 1.04–9.2, P = .04) than those with low function in the control group. Conclusion: An individualized safe‐transportation program can promote behavior change but did not translate to significant differences in weekly mileage after 12 months. Longer follow‐up may detect changes over time.